Functional connectivity studies of patients with auditory verbal hallucinations - Hoffman, Ralph E.; Hampson, Michelle (Frontiers in Human Neuroscience, 2012)
Functional connectivity (FC) studies of brain mechanisms leading to auditory verbal hallucinations (AVHs) utilizing functional magnetic resonance imaging (fMRI) data are reviewed. Initial FC studies utilized fMRI data collected during performance of various tasks, which suggested frontotemporal disconnection and/or source-monitoring.disturbances. Later FC studies have utilized resting (no-task) fMRI data. These studies have produced a mixed picture of disconnection and hyperconnectivity involving different pathways associated with AVHs. Results of our most recent FC study of AVHs are reviewed in detail. This study suggests that the core mechanism producing AVHs involves not a single pathway, but a more complex functional loop. Components of this loop include Wernicke’s area and its right homologue, the left inferior frontal cortex, and the putamen. It is noteworthy that the putamen appears to play a critical role in the generation of spontaneous language, and in determining whether auditory stimuli are registered consciously as percepts. Excessive functional coordination linking this region with the Wernicke’s seed region in patients with schizophrenia could therefore generate an overabundance of potentially conscious language representations. In our model, intact FC in the other two legs of corticostriatal loop (Wernicke’s with left IFG, and left IFG with putamen) appeared to allow this disturbance (common to schizophrenia overall) to be expressed as a conscious hallucination of speech. Recommendations for future studies are discussed, including inclusion of multiple methodologies applied to the same subjects in order to compare and contrast different mechanistic hypotheses, utilizing EEG to better parse time-course of neural synchronization leading to AVHs, and ascertaining experiential subtypes of AVHs that may reflect distinct mechanisms.